Knowledge, attitude, practice on fall prevention among informal caregivers of older person with dementia – a scoping review - Nedunsaliyan, Sankari; Ashari, Asmidawati; Ibrahim, Rahimah; Naidu, Thamayanthi (Human Resource Management Academic Research Society, 2023)
Background: Falls are a significant cause of morbidity and mortality in older people with dementia due to declining physical and cognitive abilities, exposing to high fall risk. Informal Caregivers play a crucial role in fall prevention care and their knowledge, attitudes, and practices regarding fall prevention are vital for reducing fall risks. Evaluating caregivers' knowledge, attitudes, and practices in fall prevention benefits overall care for the recipients. Objective: To identify knowledge, attitudes and practices of informal Caregivers on fall prevention among older person with Dementia and the instruments used to access it. Methods: The Arksey and O’Malley (2005) framework for scoping reviews (PRISMA-ScR) guidelines was adapted. Three databases were included in the search for articles from 2013 to 2023. Two independent reviewers conducted study selection, article screening and data extraction. Extracted data summarised according to study aim. Results: Among the 280 analysed articles, only five were relevant to our review. Five articles assessed knowledge, four assessed attitude, and three included practices related to fall prevention. However, none of the articles reported the exact instruments used for assessing knowledge, attitude, and practice. Conclusion: Key findings indicate low knowledge on fall prevention among Informal Caregivers, although they hold a positive attitude. There is a lack of practice and a multidomain approach to fall prevention. Professional references are limited, and no valid instrument to assess caregivers' knowledge, attitude and practice in preventing falls among older persons with dementia. Recommendation: Future research should focus on psychoeducation in fall prevention involving Informal Caregivers and a multidomain approach. Developing a valid instrument is essential for evaluating intervention effectiveness.